Ammonium Formate-Pd/C as a New Reducing System for 1,2,4-Oxadiazoles. Synthesis of Guanidine Derivatives and Reductive Rearrangement to Quinazolin-4-Ones with Potential Anti-Diabetic Activity - Paola Marzullo (MDPI AG, 2021)
1,2,4-Oxadiazole is a heterocycle with wide reactivity and many useful applications. The reactive O-N bond is usually reduced using molecular hydrogen to obtain amidine derivatives. NH4CO2H-Pd/C is here demonstrated as a new system for the O-N reduction, allowing us to obtain differently substituted acylamidine, acylguanidine and diacylguanidine derivatives. The proposed system is also effective for the achievement of a reductive rearrangement of 5-(2′-aminophenyl)-1,2,4-oxadiazoles into 1-alkylquinazolin-4(1H)-ones. The alkaloid glycosine was also obtained with this method. The obtained compounds were preliminarily tested for their biological activity in terms of their cytotoxicity, induced oxidative stress, α-glucosidase and DPP4 inhibition, showing potential application as anti-diabetics.